Soliton in a onedimensional force chain with Hertz contacts - Gerasymov, O.I.; Spivak, A.Ya. (Reports of the National Academy of Sciences of Ukraine, 2020)
We study comprehensively a nonlinear solitonic mode which propagates in the long-wave limit in a 1D chain of identical spherical particles interacting with each other by the Hertz law. The obtained theoretical results have been compared with relevant parameters of familiar Nesterenko’s soliton. Quantitative discrepancies between parameters of both results are outlined. Particular attention has been paid to the study of parameters which describe the impact conditions for a discrete chain and correspond to the solitonic mode generation, nonhomogeneous energy distribution, and the arrest of the solitonic energy within a particularly decorated (defected) chain. The amplitude of the soliton mode reflected from an impurity particle is estimated theoretically and found to be in a good agreement with the experimental data (much better than in analogous works).